2022
DOI: 10.1302/2633-1462.35.bjo-2022-0022.r1
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Revision Hip Complexity Classification using a modified Delphi technique

Abstract: Aims The aim of this modified Delphi process was to create a structured Revision Hip Complexity Classification (RHCC) which can be used as a tool to help direct multidisciplinary team (MDT) discussions of complex cases in local or regional revision networks. Methods The RHCC was developed with the help of a steering group and an invitation through the British Hip Society (BHS) to members to apply, forming an expert panel of 35. We ran a mixed-method modified Delphi process (three rounds of questionnaires and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The formation of complex arthroplasty networks has begun in several regions with favourable impacts reported, 10 and is supported by recent work to stratify RHA complexity. 11 We observed large variation in the RHA volume trajectories of new consultants entering practice, which is likely explained by the heterogeneous nature of clinical practice among individual consultants and the healthcare organizations in which they work. The volumes achieved by new consultants may be influenced by several different determinants, including the scope of their practice, their individual job plans, the needs of the health service or hospital, the healthcare needs of their local population, and the personal preference of a consultant to maintain a RHA practice.…”
Section: Discussionmentioning
confidence: 82%
“…The formation of complex arthroplasty networks has begun in several regions with favourable impacts reported, 10 and is supported by recent work to stratify RHA complexity. 11 We observed large variation in the RHA volume trajectories of new consultants entering practice, which is likely explained by the heterogeneous nature of clinical practice among individual consultants and the healthcare organizations in which they work. The volumes achieved by new consultants may be influenced by several different determinants, including the scope of their practice, their individual job plans, the needs of the health service or hospital, the healthcare needs of their local population, and the personal preference of a consultant to maintain a RHA practice.…”
Section: Discussionmentioning
confidence: 82%
“…24 Accordingly, techniques and multidisciplinary medical care should focus on preventing periprosthetic fracture occurrence in nonagenarians, 19 as they can lead to a devastating succession of complications and reoperations. [24][25][26] We found that medical complications were common, with an appreciable level of major complications, including cardiac ischaemia (7%) and gastrointestinal bleeding (4%). As shown by others, delirium was the most common medical complication.…”
Section: Variables Overall Revision Thas Revision Tkasmentioning
confidence: 99%
“…11 This has the advantage that a large number of individuals can contribute anonymously, without the process being dominated by a few individuals who may have particularly strong views on a topic. 12-14 In 2011, a review of the use of Delphi in healthcare provided guidance to the optimal rigorous approach for medical publications, 15 and where applicable, we have followed their recommendations. The AGREE II reporting checklist has become the internationally accepted standard for the evaluation of the methodological quality of clinical practice guidelines, 16 and we have also followed their approach.…”
Section: Introductionmentioning
confidence: 99%